Distribution system costs associated with the deployment of photovoltaic systems. (July 2018) - Horowitz, Kelsey A.W.; Palmintier, Bryan; Mather, Barry; Denholm, Paul
Abstract: The broadening of our energy system to include increasing amounts of wind and solar has led to significant debate about the total costs and benefits associated with different types of generators—with potentially far-reaching policy implications. This has included debate about the cost associated with integrating these generators onto the electric grid. For photovoltaics (PV), this encompasses costs incurred on both the bulk power and distribution systems, as well as the value provided to them. These costs and benefits, in particular those associated with integrating PV onto the distribution system, are not well understood. We seek to advance the state of understanding of "grid integration costs" for the distribution system by reviewing prior literature and outlining a transparent, bottom-up approach that can be used to calculate these costs. We provide a clear delineation of costs to integrate PV in to the distribution system within the larger context of total costs and benefits associated with PV generators. We emphasize that these costs are situationally dependent, and that a single "cost of integration" cannot be obtained. We additionally emphasize that benefits must be considered when evaluating the competitiveness of the technology in a given situation. Highlights: We review analysis on the cost to integrate PV systems on distribution networks. Costs vary significantly depending on the network and spatial distribution of PV. Costs are impacted by the strategies for incorporating the PV. Considerable variability exists in terminology and methods used in prior studies.